Protecting Marine Biodiversity: A Comparison of Individual Habitat Quotas (IHQs) and Marine Protected Areas - Kurt Schnier; Dan Holland (Fondazione Eni Enrico Mattei (FEEM), 2005)
Fisheries managers in the United States are required to identify and mitigate the adverse impacts of fishing activity on essential fish habitat (EFH). There are additional concerns that the viability of noncommercial species, animals that are habitat dependent and/or are themselves constituents of fishery habitat may still be threatened. We consider a cap-and-trade system for habitat conservation, individual habitat quotas for fisheries, to achieve habitat conservation and species protection goals cost effectively. Individual quotas of habitat impact units (HIUs) would be distributed to fishers with an aggregate quota set to maintain a target habitat stock of EFH conservation. Using a dynamic, spatially explicit fishery simulation model we explore the efficiency and cost effectiveness of an IHQ policy versus alternative marine protected area (MPA) configurations, at reducing the risk of extinguishing a habitat dependent species of unknown spatial distribution. Our findings indicate that an IHQ policy with a conservatively established habitat target is better suited to the protection of non-target species than a rotating or fixed MPA policy.
Keywords: Q20; Q22; 330; Fisheries management; Individual transferable quota; ITQ; Individual habitat quota; IHQ; Essential fish habitat; EFH; Marine protected areas; MPA; Non-target species; Biodiversität; Fischerei; Quotenregulierung; USA